2002
DOI: 10.1590/s0104-79302002000200007
|View full text |Cite
|
Sign up to set email alerts
|

Some toxinological aspects of Aurelia aurita (Linné) from the Mexican Caribbean

Abstract: Aurelia aurita is a scyphozoan, abundant in the Mexican Caribbean during summer. Although usually innocuous, there is evidence of it causing harm to humans. This work investigates the biological activities of crude and fractionated extracts of A. aurita. Live specimens were collected between July and September 1999 from the Mexican Caribbean. The tentacular margin was dissected immediately and frozen at -50ºC. A nematocyst suspension was prepared, discharged, and the supernatants lyophilized. Hemolytic assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…Size exclusion chromatography and gel electrophoresis of the bioactive venom were performed by Segura-Puertas et al (2002) and indicated that the toxic proteins were 45 and 66 kDa which matches the detected values in the present investigation. The broad molecular weight range (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Size exclusion chromatography and gel electrophoresis of the bioactive venom were performed by Segura-Puertas et al (2002) and indicated that the toxic proteins were 45 and 66 kDa which matches the detected values in the present investigation. The broad molecular weight range (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…A general lytic effect was observed when red-tide flagellate species were treated with A. aurita autolysate (Hiromi et al, 1997). Segura-Puertas et al (2002) found that dermonecrotic activity, haemolysis and neurotoxicity were caused by exposure to whole venoms of tentacular margins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and suggested that different diets during the growth of the medusae may be responsible for the different frequencies of nematocyst types. Furthermore, Burnett et al (1988), Radwan et al (2001), andSegura-Puertas et al (2002) suggested that the variation in stinging potency and toxic potential in the medusae they studied was related to their different habitat conditions. The objective of this study was to compare the cnidom and the capsule contents of separated nematocysts of C. capillata (L.) medusae collected from the North Sea and from the Baltic Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Many species of jellyfish are known to cause injuries or even fatalities by stinging (Burnett et al, 1988;Fenner, 1998;Segura-Puertas et al, 2002;Tibballs, 2006;Š uput, 2009). Despite the wide-spread concern about the damage caused by jellyfish stings to the tourism and aquaculture industries (Doyle et al, 2008), surprisingly little is known about the effect of various environmental factors on the toxins of the medusae.…”
Section: Introductionmentioning
confidence: 99%